Green and Efficient Synthesis of Novel Pyrazole based Hydrazineyl-Thiazole Derivatives - Dipak P. Hiwarale; Wilson B. Chandane; Dattatraya G. Raut; Shivanand G. Sonkamble (International Journal of Scientific Research in Science and Technology, 2025)
A green and efficient protocol for the synthesis of novel pyrazole based hydrazineyl-thiazole derivatives via a two-step procedure is reported. The reaction has been catalyzed by p-TSA using ethanol as green solvent. The present protocol offers several advantages such as broad substrate scope, operational simplicity, high yields and use of environmentally benign solvent.
Keywords: Green synthesis; Pyrazole; p-TSA; hydrazineyl-thiazoles